FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN LAPORAN KEBERLANJUTAN (STUDI PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2017) - Arini Jembar Rahayu; Cahyaningsih - (JAF (Journal of Accounting and Finance), 2020)
The research objective is to determine the effect of sales growth, profitability, corporate governance, and company size simultaneously and partially on the sustainability report of non-financial companies listed on the Indonesia Stock Exchange for the period of 2016-2017. The method used is panel data regression analysis and the results of the study found that simultaneous sales growth, profitability, corporate governance, and company size influence the disclosure of sustainability reports. Partial testing only profitability and company size that affect the disclosure of sustainability reports.